Prevalence, intensity, and associated factors of intestinal schistosomiasis among primary school children in Nono District, Southwest Ethiopia - Tolera, Bayisa; Mohammed, Jemal; Umer, Ukash; Abamecha, Junedin; Tebeje, Fikru; Sime, Akewok; Weldegebreal, Fitsum (Frontiers in Tropical Diseases, 2025)
BackgroundIntestinal schistosomiasis caused by Schistosoma mansoni is a common helminthic infection recognized as an important public health problem in tropical and subtropical regions, particularly in sub-Saharan Africa, including Ethiopia. The disease is highly prevalent among schoolchildren with emerging data showing that these population groups are infected and carry heavy infection intensities. However, there was no prior data on this infection’s extent, intensity, and predisposing factors in the current study area. Therefore, this study aimed to assess the prevalence, intensity, and associated factors of intestinal schistosomiasis among primary school children in Nono District, Southwest Ethiopia.MethodsA school-based cross-sectional study was conducted from January 20 to February 20, 2024 with 338 randomly selected primary school children. Data on socio-demographic and potential predisposing factors were collected using a structured questionnaire. A total of 5 g of stool samples was collected and processed using the Kato-Katz technique for parasitic investigation and infection intensity. Data were entered into Epi-data version 3.1 and then exported to Statistical Package for the Social Sciences version 26 for analysis. Binary logistic regression analyses were carried out to examine the associations between dependent and independent variables. A P-value <0.05 was considered statistically significant.ResultsIn this study, only 21.5% of participants were infected with S. mansoni (95%CI: 11.77, 32.47). Of those infected participants, 49.3% had light infection intensity. Children who had no habit of wearing shoes (AOR = 3.27, 95%CI: 2.04, 8.47), wear shoes sometimes (AOR = 1.87, 95%CI: 1.22, 7.31), had open defecation practice at school (AOR = 1.21, 95%CI: 1.02, 3.58), from families who used river (AOR = 5.47, 95%CI: 2.53, 9.76) and spring water (AOR = 1.28, 95%CI: 1.01, 3.88) for drinking, from families who had no latrine at home (AOR = 8.14, 95%CI: 4.03,10.94), who had bathing habit in open water source once per day (AOR = 5.29, 95%CI: 3.01, 11.49), twice per week (AOR = 3.42, 95%CI:1.98, 7.92), and once per week (AOR = 2.56, 95%CI: 1.07, 5.96), and who did not know the possible modes of transmission (AOR = 1.15, 95%CI: 1.04, 3.27) were significantly associated with intestinal schistosomiasis.ConclusionThe prevalence of S. mansoni infection in this study was medium according to the WHO (2022) classification. Factors like having no habit of wearing shoes, using river and spring water for drinking, having open defecation practice at school and home, bathing in open water sources, and not knowing the possible modes of transmission aggravated the occurrence of intestinal schistosomiasis. Therefore, health education should be given to children on the importance of wearing shoes, improving water sources, and environmental sanitation to alleviate the problem.